2012
DOI: 10.1017/s0025315412000902
|View full text |Cite
|
Sign up to set email alerts
|

Distribution related to temperature and salinity of the shrimps Acetes americanus and Peisos petrunkevitchi (Crustacea: Sergestoidea) in the south-eastern Brazilian littoral zone

Abstract: The abundance and ecological distribution of Acetes americanus and Peisos petrunkevitchi were investigated from July 2006 to June 2007, in Ubatuba, Brazil. Eight transects were identified and sampled monthly: six of these transects were located in Ubatuba bay, with depths reaching 21 m, and the other two transects were in estuarine environments. A total of 33,888 A. americanus shrimp were captured, with the majority coming from the shallower transects (up to 10 m). Conversely, 6,173 of the P. petrunkevitchi sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
3
13
0
6
Order By: Relevance
“…In the Lagoa dos Patos study, the temperature varied from 13.2 to 24.9º C, and the greatest abundance of A. americanus larvae was registered at 20.7º C. In Ubatuba, SIMÕES (2013b) found that the temperature varied from 21.9 to 26.2º C, and that the greatest abundance of A. americanus occurred at temperatures closest to 24.5º C. We suggest that, because the region of Macaé (22ºS) experiences low temperatures throughout most of the year, the species' preference for this region may be due to the fact that the population can tolerate this variation in temperature. Laboratory experiments performed by Bhattacharya (1988) (apud XIAO;GREENWOOD, 1993) have shown that A. indicus can tolerate temperatures between 14.0º C and 34.0º C. XIAO;GREENWOOD (1993) reported that A. chinensis from Laizhou Bay in the south of Pohai tolerates an annual temperature variation from -0.1º C to 29.5º C. In addition to environmental factors such as temperature, the presence or absence of predators may also be responsible for variations in the collected quantities of sergestid shrimp (XIAO; GREENWOOD, 1993).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the Lagoa dos Patos study, the temperature varied from 13.2 to 24.9º C, and the greatest abundance of A. americanus larvae was registered at 20.7º C. In Ubatuba, SIMÕES (2013b) found that the temperature varied from 21.9 to 26.2º C, and that the greatest abundance of A. americanus occurred at temperatures closest to 24.5º C. We suggest that, because the region of Macaé (22ºS) experiences low temperatures throughout most of the year, the species' preference for this region may be due to the fact that the population can tolerate this variation in temperature. Laboratory experiments performed by Bhattacharya (1988) (apud XIAO;GREENWOOD, 1993) have shown that A. indicus can tolerate temperatures between 14.0º C and 34.0º C. XIAO;GREENWOOD (1993) reported that A. chinensis from Laizhou Bay in the south of Pohai tolerates an annual temperature variation from -0.1º C to 29.5º C. In addition to environmental factors such as temperature, the presence or absence of predators may also be responsible for variations in the collected quantities of sergestid shrimp (XIAO; GREENWOOD, 1993).…”
Section: Discussionmentioning
confidence: 91%
“…Little is known of the biology of A. americanus, and the studies that have been performed in Brazil have focused on faunal composition, descriptions of the larvae, and geographical distribution (CALAZANS, 1992;OSHIRO;OMORI, 1996;MARTINS, 2000). SIMÕES et al (2013a;2013b) undertook two studies on the spatio-temporal distribution, juvenile recruitment period, and growth of the species along the northern coast of São Paulo state. The greatest abundance of A. americanus was observed in shallow waters less than 10 meters deep, at temperatures between 16.0 and 30.0º C, and in waters with salinity levels between 22.0% and 38.0%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant frequency of occurrence of the Sergestidae from the genus Acetes is related to the fact that they occupy the epipelagic or the mesopelagic zones ( Simões et al, 2012), being widely consumed also by the seabob-shrimp Xiphopenaeus kroyeri (Branco 2005). Xiao and Greenwood (1993) studying the biology of Acetes, observed a clustering behavior in various spatial and temporal scales.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was found by Rodrigues and Meira (1988), with the presence of the seabob shrimp in only 22 of the 77 analyzed stomachs of S. rastrifer and 2 of the 36 analyzed stomachs of S. basiliensis. It is known that penaeid shrimps are benthic and burry themselves in the sediment (Castilho et al, 2008;Simões et al, 2012), and therefore are available in a smaller scale for benthopelagic consumers, such as S. rastrifer and S. brasiliensis (Wakabara et al, 1993). Even if juveniles of X. kroyeri, are available in the pelagic zones for these fishes, they may be choosing to consume shrimp from the genus Acetes not only for their abundance in the studied environment, but for their short and blunt rostrum, that are of easier consumption than the sea-bob's rostrum with five teeth near the base and slightly curved upwards.…”
Section: Discussionmentioning
confidence: 99%